Pelatihan Perpajakan untuk Meningkatkan Kompetensi Siswa Siswi SMK di Jakarta dan Tangerang - Meiriska Febrianti; Silvy Christina; Haryo Suparmun; Rian Sumarta (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Tax is an important role for a country, because the main source of state revenue is obtained from the tax sector. To support state revenues from the taxation sector, taxpayer awareness and compliance is required, both in terms of calculation, deposit and tax reporting. Trisakti School of Management through P3M (Center for Community Research and Development) implementing the tri dharma of higher education is also responsible for being able to play a role in providing an understanding of taxation for the community through Community Service activities. The purpose of this community service activity is to provide knowledge and understanding of tax rights and obligations, namely regarding the calculation and filling of the Annual Income Tax Return for Individuals. The methods used in this training are through lectures, practice case studies and question and answer. The result achieved in this training activity is that the participants can understand how to calculate and fill out the Annual Personal Income Tax Return using forms 1770SS and 1770S. The expected targets and outcomes for participants in this training are participants can understand their tax obligations, and have the awareness to fill out Annual Tax Returns independently, completely and correctly so that taxpayer reporting compliance also increases.